Some trends in the formation of Surinkimininkai literature in Prussian Lithuania: links with the Western tradition and local innovations - Sidabraitė, Žavinta; Rekašiūtė, Kotryna (Senoji Lietuvos literatūra, 2018)
The Pietist movement Surinkimai in Prussian Lithuania lasted approximately from the middle of the eighteenth century to the end of the Second World War. The literature answering the needs of Surinkimininkai was translated, written, and published for about the same duration of time. For the Lithuanian Surinkimininkai, the most preferred genre was the hymn that to some extent replaced the folk song in their daily life. The hymnal Visokios naujos giesmės arba evangeliški psalmai (Various New Hymns or Evangelical Psalms) by Kristijonas Endrikis Mertikaitis (about 1775 – before 1856) should be considered the absolutely most popular book among the Surinkimininkai. Later, various genres of prose became popular: catechisms, sermons and their collections, moral educational literature, as well as biographies, travelogues, and preachers’ letters. More voluminous works were mostly translated literature that had evolved from the tradition of medieval mysticism or was part of it (works by Johann Arndt, Thomas von Kempen, and others). The so-called burtikės, much liked by the Surinkimininkai, should be seen as an original genre of Lithuanian literature: burtikės was a collection of cards, each card bearing maxims from the works by Martin Luther, hymnals, or other religious literature. Despite their religious content, burtikės were associated with the sphere of magic: by drawing them, people predicted the future, checked the decisions made, and the like. The biographies of the preachers spread by word of mouth among the Surinkimininkai. These were folk stories formed on the examples of the descriptions of the lives of the ‘new saints’, of biblical texts about the apostles, and of the Catholic narratives about the saints. The outbreak of creative folk energy allows considering these biographies of the preachers or other betterknown pious heroes an original alternative of the myth or the fairy-tale. In Prussian Lithuania, the Surinkimininkai movement was mostly a ‘bottomup’ one; it was a movement of the people, and therefore for the first time in the literary history a fair amount of literature was translated not by pastors but by laymen – teachers and sometimes farmers. The urge of a rather poorly educated enthusiast from the people to take up written work should be seen as a response to the needs of equally poorly educated reader at the time of the rise of a reading and writing society. Naïve and simple, at times too sentimental, the literature of the Surinkimininkai formed a stylistic alternative to the refined, strict, and rational Classicist aesthetics and should be considered as the first shoots of sentimental aesthetics in Lithuanian literature.
Keywords: pietism; surinkimininkai; Lithuanian literature; hymns; biography; preacher; Johann Arndt; mysticism; sentimentalism